Analisis Profitabilitas Usahatani dan Pemasaran Kacang Tanah di Kecamatan Pujananting Kabupaten Barru - Muchtar, Nur Afni Syahrin; Rukmana, Didi; Summase, Idris (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
Peanuts are one of the agricultural commodities that have high economic value. The need for peanuts continues to increase every year along with population growth, community nutritional needs, and the development of the feed and food industry in Indonesia. Optimal peanut production can improve farmers' welfare. However, income from peanut farming is not only influenced by the level of production, but also by the marketing method of the agricultural products. South Sulawesi is the second largest peanut producing province outside Java, with Barru Regency as its leading area. The purchase price of peanuts often fluctuates every year, and the selling price tends to be low during the peak harvest season, so farmers do not get profitable prices. This study aims to (1)Analyze the level of profit of peanut farming, (2)Analyze peanut marketing channels, and (3)Determine the efficiency of peanut farming marketing channels. The method used is quantitative descriptive analysis with the help of the Microsoft Excel application. The research location is in Pujananting District, Barru Regency, with 96 farmer respondents and 9 marketing institutions. The results of the study showed that (1) Peanut farming in Pujananting District, Barru Regency, was profitable with an R/C ratio of 2.52%; (2) There were 2 marketing channel patterns, namely marketing channel (I) involving farmers, retailers, and consumers, while marketing channel (II) involved farmers, collectors, wholesalers, and industry.; (3) The most efficient marketing channel was marketing channel I with an efficiency value of 1.64%.